Literature Study: Global Financial Crisis and Islamic Finance As A Solution - Dedy Dwi Arseto; Nirmadarningsih Hiya; M. Sabri Abd. Majid; Marliyah Marliyah; Rita Handayani (Jurnal AKTUAL, 2022)
Literature Study: Global Financial Crisis and Islamic Finance As A Solution. One of the basic tenets of Islamic finance is "no risk, no gain". This will help. Since interest-based transactions are prohibited, Islam encourages business and trade activities that generate fair and legitimate profits. In Islamic finance, therefore there is always a close relationship between financial flows and productivity. This intrinsic property of Islamic finance contributes to protecting it from the potential risks of over-leverage and speculative financial activities that are part of the root causes of the current financial crisis. Another fundamental principle of Islamic finance is the risk and profit sharing feature of Islamic financial transactions (such as Mudharabah or Musyarakah contracts). This feature of sharing the benefits and risks of Islamic financial transactions requires a high level of disclosure and transparency in the Islamic financial system. This disclosure allows the market to assign an appropriate risk premium to the company, thereby increasing the potential for applying market discipline. Its rapid evolution is mainly seen in the four dimensions of its development. First, Islamic finance is currently seen as a competitive form of financial intermediation, which attracts significant participation by non-Muslims. Second, with the emergence of more diversified Islamic financial institutions and the development of Islamic financial markets, the scope of the Islamic finance business has expanded to include private equity, project financing, origination and issuance of sukuk (bonds), and funds, assets. , and wealth management activities. The third place where there has been a significant evolution is within the regulatory and legal framework of Islamic finance, which is shaped by the different features of Islamic financial transactions. Fourth, the international dimension of Islamic finance is rapidly becoming important as it develops into an increasingly important part of the international financial system and as it is poised to contribute to greater global financial integration. KEYWORDS: Financial Crisis, Islamic Finance